Preservation of Eggs Using Chitosan and Its Application in Angel Cake - Bani, N.A.I.S.; Hatta, W.; Nahariah, N. (Hasanuddin Journal of Animal Science (HAJAS), 2025)
Eggs are easily damaged because of their high nutritional content, particularly their protein content. Therefore, preservation methods are necessary, with one such method involving the use of chitosan to prolong the freshness of the eggs while preserving their quality. This study aimed to assess and compare the efficacy of chitosan in maintaining the quality of purebred chicken eggs when stored at room temperature and its application in processed angel cake products. The experimental approach employed for egg preservation was a completely randomized design (CRD) with four treatments (P0 = no treatment, P1 = 1% chitosan solution, P2 = 2% chitosan solution, and P3 = 3% chitosan solution), replicated five times. The data underwent variance analysis, followed by Duncan's test to ascertain the impact of chitosan on egg preservation and product quality. The results revealed a significant effect (P<0.05) of chitosan solution on egg weight loss, Haugh unit, yolk index, and egg pH. Notably, 3% chitosan was more effective in maintaining egg quality than 1% and 2% chitosan coatings. In the 3% treatment, egg weight loss only experienced a shrinkage of 2.57% or 1.67 g from the initial egg weight. Haugh Unit of 65.57, yolk index of 0.41, and egg pH of 7.98. Additionally, angel cake products made from preserved eggs using chitosan exhibited significant differences (P < 0.05) compared to those made from fresh eggs. The panelists preferred the texture and organoleptic attributes of the angel cake prepared with chitosan-preserved eggs. Keywords: Chitosan, egg interior quality, angel cakes, texture profile